The main methodological approaches to the formation of universal competencies of students of technical universities - Anna S. Tuchkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper highlights the theoretical provisions describing the main methodological approaches to the formation of competencies, which are provided for by modern federal state educational standards of higher education, taking into account professional standards (FGOS HE (3++)) bachelors degree in the areas of training of the enlarged group 090000 Computer Science and Computer engineering: competence, system-activity and information approaches in education and pedagogical science. The differences between the analyzed FGOS in (3++) and earlier educational standards in the aspect of the formed results of educational activity are highlighted. The concept of competence itself is clarified, the views of scientists on the content of this term given in domestic and foreign literature are analyzed. The result of educational activity is considered as a set of competencies formed in the process of educational activity aimed at the implementation and application of professional skills of a future specialist in a certain subject area. Attention is drawn to the possibilities of the listed methodological approaches to the organization and implementation of the educational process in the formation of interdisciplinary and suprasubject competencies, which is required by modern conditions: the future specialist must be competitive, meet the needs of the employer, have opportunities for self-realization, etc. these opportunities are described by the example of curricula adopted for implementation in the Volga State University of Telecommunications and computer science. The necessity of integration of individual approaches in order to effectively implement educational activities is substantiated. It is noted that the need for effective organization of the modern digital educational process requires scientific justification. In this regard, the development of digital didactics, a new and relevant direction of pedagogical science, is being noted today.